Foodborne disease outbreaks in the Philippines (2005-2018) - Azanza, Maria Patricia V.; Membrebe, Bernard Niño Q.; Sanchez, Rowena Grace R.; Estilo, Emil Emmanuel C.; Dollette, Una Grace M.; Feliciano, Rodney J.; Garcia, Nadine Kristel A. (2019)
The study detailed 209 reported Philippine foodborne disease outbreaks (FBDOs) for the period 2005 – Jun 2018. Multiple implicated foods were associated in majority of the studied outbreaks. Meat-containing dishes were the most common causative foods in the evaluated outbreaks with defined food vehicles. Food service eating facilities and households were found more prone to outbreak occurrences. Although there were reported outbreaks with unidentified causative agents, Salmonella spp., Henipavirus, Entamoeba histolytica, and Vibrio parahaemolyticus were cited as primary causes of infections. Human intoxications involved staphylococcal enterotoxins, carbamate toxin, and paralytic shellfish poisoning (PSP) toxin. Impact of the study on the implementation of national food safety controls of the Philippines was also cited.
Keywords: Foodborne diseases; Food safety